Beyond reengineering how the process-centered organization is changing our work and our lives - Hammer, Michael (New York HarperBusiness, 1997)
Reengineering has captured the imagination of managers and shareholders alike, sending corporations on journeys of radical business redesign that have already begun to transfigure global industry. Yet aside from earning them improvements in their business performance, the shift into more-process-centered organizations is causing fundamental changes in the corporate world, changes that business leaders are only now beginning to understand. What will the revolutions final legacy be? Beyond Reengineering addresses this question, exploring reengineering's effects on such areas as
Includes index
Keywords: Reengineering (Management); Organizational change; Industrial organization